2022
DOI: 10.1186/s42269-022-00964-0
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance and flexural strength of endodontically treated teeth restored by different short fiber resin composites: a preclinical study

Abstract: Aim To evaluate the effect of using different short fiber-reinforced resin composites on fracture resistance and flexural strength of endodontically treated tooth and compare it with nano-filled resin composite. Methods Sixty human premolars were used for the fracture resistance test. Root canals were sequentially enlarged using a Pro-taper system from SX to F3 and obturated with Gutta-percha. Mesio-Occluso-Distal (MOD) cavities were prepared in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The results of this study showed that the group of Ever X Flow had highest fracture resistance with no signi cant difference when compared with packable owable composite group, this result approved many other studies [19] [21], on contrary, many studies showed signi cant difference between reinforced composite -which had the highest fracture resistance-and other types of composites [5] [18], these difference with this study can be substantiated, on one hand, of the variation of restoration materials used in various studies, for example, farhanny et al study had three groups two of them used conventional bulk-ll composite and the third one was Ever X Posterior, whereas this study used Ever X Flow composite and compared it with one type of bulk-ll owable composite, on the other hand, of the difference coronal cavities design, lassila et al study evaluate the fracture behavior of direct composite restorations made with two different composite core materials, whereas, MOD traditional preparation cavities used in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study showed that the group of Ever X Flow had highest fracture resistance with no signi cant difference when compared with packable owable composite group, this result approved many other studies [19] [21], on contrary, many studies showed signi cant difference between reinforced composite -which had the highest fracture resistance-and other types of composites [5] [18], these difference with this study can be substantiated, on one hand, of the variation of restoration materials used in various studies, for example, farhanny et al study had three groups two of them used conventional bulk-ll composite and the third one was Ever X Posterior, whereas this study used Ever X Flow composite and compared it with one type of bulk-ll owable composite, on the other hand, of the difference coronal cavities design, lassila et al study evaluate the fracture behavior of direct composite restorations made with two different composite core materials, whereas, MOD traditional preparation cavities used in this study.…”
Section: Discussionsupporting
confidence: 80%
“…However this technique pose a high risk of debonding in case of minor injuries [ 17 ]. hence the anterior restorative material should not only be esthetic and but also able to endure the impact forces during re-trauma [ 18 ]. In the past, attempts have been made to improve the load-bearing capacity of restoration by using different bonding systems and adhesive resins.…”
Section: Introductionmentioning
confidence: 99%